A facile one-step synthesis of chromeno[4,3-b]pyridine derivatives promoted by niobium pentachloride - Oshiro, Paula B. [UNESP]; Bregadiolli, Bruna A. [UNESP]; da Silva-Filho, Luiz C. [UNESP] (Wiley, 2020)
Chromenes are part of an important class of heterocyclic compounds, natural or synthetic, and have many biological and chemical applications. Among them, chromenopyridines has arisen as a promising material for pharmacological applications. In this work is described a simple and cost-effective method to synthesize chromeno[4,3-b]pyridine derivatives from multicomponent reaction between 4-aminocoumarin, benzaldehyde derivatives, and ethyl benzoylacetates catalyzed by niobium pentachloride. The new method provides good yields with reasonable reaction times, under mild reaction conditions.